PEMANFAATAN IKAN MANYUNG (Arius thalassiunus) SEBAGAI PUPUK BOKASHI UNTUK MEDIA TANAM BIBIT TREMBESI (Samanea saman) - La-Upe, Muhammad Fajar Rahman; Achmad, Basir; Rukmini, Rukmini; Biyatmoko, Danang (Universitas Lambung Mangkurat, 2024)
Kusan Hilir Sub-district is one of the coastal sub-districts in Tanah Bumbu Regency where most of the people work as fishermen. Fish caught by fishermen that do not have high selling value such as otek fish or manyung fish, and tembang fish or sardinella fish are often thrown into the sea so that they can pollute marine waters. The remaining fish or fish that are wasted have organic value, both organic-N, organic-P, and organic-K. The purpose of this study was to analyze the effect of using otek fish bokashi, firewood husks, and subsoil soil on the growing power of trambesi plants and determine the best composition of fish bokashi produced based on biomass in plants. The research was carried out using the Completely Randomized Design (CRD) method with 6 treatments and 5 replications with 3 plants and placed randomly by doing random numbers in the excel application with the treatment code P0 100% subsoil soil, 0% fish bokashi, 0% burnt husk, P1 subsoil 90%, fish bokashi 5%, burnt husk 5%, P2 subsoil 80%, fish bokashi 10%, burnt husk 10%, P3 subsoil 70%, fish bokashi 15%, burnt husk 15%, P4 subsoil 60%, fish bokashi 20%, burnt husk 20%, and P5 soil 50%, fish bokashi 25%, burnt husk 25%. Data analysis used in this study used the Anova test followed by the DMRT (Duncan Multiple Range Test) test. The results of observations or weighing on the wet weight and dry weight of plant biomass show that the treatment with the composition of 50% soil planting media, 25% fish bokashi, 25% burnt husk with an average wet weight of 174.44g and a dry weight of 88.64g has a very significant effect on 90 day trambesi seedlings, although the treatment with the composition of 90% subsoil soil planting media, 5% fish bokashi, 5% burnt husk, and the composition of 80% subsoil soil planting media, 10% fish bokashi, 10% burnt husk is not significantly different.